The New Generation of Professional Soccer Talent Is Born under the Bias of the RAE: Relative Age Effect in International Male Youth Soccer Championships - Benito Pérez-González; Jairo León-Quismondo; José Bonal; Pablo Burillo; Álvaro Fernández-Luna (Children, 2021)
In 2019, numerous championships of youth categories soccer national teams were held. In the present study, we analyzed the existence of the Relative Age Effect (RAE) in four major male championships that, due to their importance and participating teams, most likely brought together the great bulk of the players who will dominate professional soccer in the next decade. Participants were professional and amateur youth male soccer players who participated in the last international championships: UEFA European Under-21 Championship (2017–2019); UEFA European Under-19 Championship (2019); South American Youth Football Championship (also known as Conmebol U-20) (2019); and FIFA U-20 World Cup (2019), with 823 players (20.25 ± 0.84 years). In the four championships analyzed, the existence of RAE was found for all players (p < 0.001). Analyzing the players when considering their position on the pitch and their championship, RAE was found, statistically significant, in 10 of the 16 classifications. New generations of elite soccer players arrive with a clear bias in the selection of talent; an unfair bias, based on unequal opportunities in early categories, which should be reviewed by sports authorities.